Penciptaan Lakon Parashurama - Aan Bagus Saputro; Jaka Rianto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2021)
The presentation of Parashurama, universally, tells about the loyalty, dharma of life and tolerance possessed by the figure of Rama Bargawa. The message conveyed in this Lakon Parashurama is about the great respect for the country and parents. Parashurama’s creation uses the form of pakeliran padat with the methods of observation, interviews and data analysis. The results show that Parashurama’s work is able to provide a presentation with complex problems in life, namely loyalty. Parashurama’s inner conflict between the two choices is solved by holding on to the dharma that must be held in life.